2021
DOI: 10.3390/app11198825
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Approach to the Analysis of the Corrosive Behaviour of NiTi Alloys under the Influence of Different Seawater Environments

Abstract: Probabilistic models of corrosion rate estimation in the case of two NiTi alloys obtained by different technological processes are analysed in this paper. The depth of corrosion was measured by focused ion beam analysis on a metal surface that was not protected by an anti-corrosion coating. The samples were exposed to the influence of three different seawater environments, and empirical data were obtained in a systematic measurement procedure after 6, 12 and 18 months. Assuming that corrosion processes begin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In the present study we compared the biofunctional properties of nickel–titanium alloys obtained by two different production processes. Contrary to conventional casting, continuous casting was previously reported to be a production process that was able to produce stands of relatively small diameter with an acceptable surface quality [ 17 , 25 , 26 ]. Even though the correlation between production processes and material properties has been proven in numerous studies [ 27 , 28 ], there is still no clearly defined consensus on the accepted model for the production of these alloys for application in dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we compared the biofunctional properties of nickel–titanium alloys obtained by two different production processes. Contrary to conventional casting, continuous casting was previously reported to be a production process that was able to produce stands of relatively small diameter with an acceptable surface quality [ 17 , 25 , 26 ]. Even though the correlation between production processes and material properties has been proven in numerous studies [ 27 , 28 ], there is still no clearly defined consensus on the accepted model for the production of these alloys for application in dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated a higher hardness of NiTi-2 in comparison to the NiTi-1 alloy. This can be explained by a higher nickel content, and/or iron content, as shown by EDX/XRF analysis, which is in agreement with previous reports [ 25 , 26 ]. An additional EBSD analysis revealed that there were two phases in the microstructure of NiTi-1 samples (NiTi-cubic and Ni 3 Ti hexagonal), while an additional NiTi 2 -cubic phase was detected in the NiTi-2 microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…A conceptual research model that follows the research methodology from this paper is presented in Figure 2. In our previous article [20], a similar methodology was used in the case of a CuAlNi alloy. While conducting the experiment between August 2019 and March 2020, the parameters of the seawater salinity were measured under the "Coastal Sea Ecosystem Monitoring Program of Montenegro", at the Institute of Biology, University of Montenegro.…”
Section: Methodsmentioning
confidence: 99%
“…The material used in this research was exposed to a real marine environment in the form of standardized coupons [37] for a period of two years, with testing and analysis performed after 6, 12, and 24 months. Most studies concerned with the environmental degradation of the material properties were based on laboratory experiments and either simulated real environments [38] or were conducted in an accelerated manner [39]. Since marine structures need to operate in corrosive environments for long periods, there is a certain gap in research when it comes to experiments that are conducted in the natural environment for prolonged periods [40].…”
Section: Experimental Investigationmentioning
confidence: 99%